A randomized controlled trial for families with preschool children - promoting healthy eating and active playtime by connecting to nature. (December 2016) - Sobko, Tanja; Tse, Michael; Kaplan, Matthew
Abstract Background Promotion of healthy lifestyles in children focuses predominantly on proper nutrition and physical activity, elements now widely recognised as essential for a healthy life. Systematic reviews have shown that nature-related activities also enhance general well-being as reflected in increased physical activity, a healthier diet, reduced stress and better sleep. Recent research suggests that many young children in Hong Kong between the ages of two and four in Hong Kong are more sedentary than recommended and seldom participate in active play, placing them at risk of becoming overweight or obese. The proposed project aims to investigate whether connecting families to nature positively influences physical activity (i.e., active playtime) and healthy eating routines in children aged 2 to 4. Methods We recently conducted a pilot study in Hong Kong to develop a programme, Play & Grow, based on the most successful evidence-based international preschool interventions. In addition to adopting the healthy eating and physical activity elements of these interventions, this project will additionally include a third novel element of Connectedness to nature: discovering nature through games and awareness of sounds, touch, smells, and temperature. To test the effectiveness of this modified intervention, a randomised controlled trial (RCT) involving 240 families with children aged 2 to 4 will be conducted. Families and children will take part in weekly one-hour activity sessions for 10-weeks. Lifestyle-related habits will be assessed before and immediately after the 10-week intervention, with follow up testing at 6 and 12 months' post intervention. Discussion A novel measuring tool created specifically for assessing Connectedness to nature, Nature Relatedness Scale (NRS), will be validated and tested for reliability prior to the RCT. The results of the RCT are intended to be used to understand which components of the intervention are most effective. The objectives of this project will be achieved over a 30-month period and will contribute to the research that examines key components of successful healthy lifestyle promotion programmes during early childhood. We predict that the inclusion of Connectedness to nature will significantly improve recognised preschool interventions. Finally, the aim of targeting family involvement will hopefully increase the sustainability of longer-term lifestyle modifications in children. Trial registration ClinicalTrials.gov, NCT02715544 . Registered 22 March 2016